Exploring the landscape of educator professional activity on Twitter: an analysis of 16 education-related Twitter hashtags. Issue 5 (20th October 2022) - Carpenter, Jeffrey; Tani, Tania; Morrison, Scott; Keane, Julie
ABSTRACT: In the last decade, social media have become important tools for educator professional development, learning and community. While education has traditionally proven to be an isolating profession, technologies such as Twitter offer opportunities for educators to collaborate beyond their school, district, region and nation. Education-related Twitter hashtags play a key role in facilitating professional connections and interactions between geographically-dispersed educators with common interests and needs. To better understand this phenomenon, we examined more than 2.6 million tweets posted to 16 such education-related hashtags over a 13-month time period. We compared and contrasted synchronous and asynchronous uses of the hashtags, as well as the balance of tweets and retweets, among other characteristics of the hashtag usage. Across the combined hashtags, there was an increase in traffic and trends towards more retweeting and less original tweeting and link sharing. There were substantial differences in the traffic associated with the various hashtags. We discuss our findings in relation to the professional learning and development literature and consider implications for the research and practice of prospective and practicing teacher development in online spaces.